Cardiorespiratory fitness and left ventricular function in breast cancer survivors a decade after Epirubicin treatment. (3rd October 2022) - Saeter, M; Nilsen, T S; Johansen, S H; Thorsen, L; Reinertsen, K V; Haugaa, K H; Edvardsen, T; Sarvari, S I
Abstract: Background: Anthracyclines are effective chemotherapeutic agents commonly used in breast cancer (BC) treatment. Cardiotoxicity is a serious adverse effect of anthracyclines, but knowledge of long-term cardiac effects is limited. To our knowledge, no prior study has investigated both cardiorespiratory fitness assessed by peak oxygen consumption (V̇O2 peak ) and left ventricular (LV) function in long-term follow up of BC survivors (BCS) treated with anthracyclines. Purpose: To assess long-term adverse effects of Epirubicin on cardiorespiratory fitness and LV function in BCS. Methods: The CAUSE-trial is an ongoing study comparing exercise effects in BCS of stage I-III BC recruited from the Cancer Registry of Norway and controls with no cancer diagnosis. We present preliminary results from the baseline assessments in this trial. BCS (n=93) treated with Epirubicin between 2008 and 2013 were compared to age-matched controls (n=11). V̇O2 peak was assessed by incremental treadmill cardiopulmonary exercise test and LV function by echocardiography. Results: At baseline, BCS were 58±7 years old and had received a cumulative dose of 339±85 mg/m 2 Epirubicin 11±1 years before examination. There was no difference in V̇O2 peak between BSC and controls. LV ejection fraction was lower in BCS compared to controls assessed by 2D (57±3% vs. 59±2%, p=0.01) and 3D echocardiography (57±3% vs. 61±4%, p=0.006). LV global longitudinal strain was also lower (in absolute value) in BCS compared to controls (−20.6±1.3% vs. −22.0±1.3%, p=0.002). There was no difference in global work index and efficiency between BCS and controls. Conclusion: Our findings indicate no difference in cardiorespiratory fitness between BCS and controls a decade after Epirubicin treatment. Systolic LV function was slightly lower in BCS compared to controls. Importantly, systolic LV function in BCS was within normal range, and the difference is probably not of clinical importance. There was no difference in myocardial work between BCS and controls. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): The Cancer Registry of Norway